Reduction of carbon dioxide to dimethylformamide using ruthenium doped Mg/Al hydrotalcites under supercritical conditions - Chaudhary, Sagar D.; Rahatade, Shardul S.; Joshi, Sunil S.; Mali, Nilesh A. (Journal of CO2 Utilization, 2022)
The utilization of carbon dioxide is one of the developing areas due to its significant contribution to global warming. Reducing carbon dioxide (CO2) to formic acid and its derivatives has gained importance because of its thermodynamic limitations and high industrial demand. In this article, we report the synthesis of dime-thylformamide (DMF) using ruthenium doped Mg/Al calcined hydrotalcite by CO2 hydrogenation in the presence of dimethylamine (DMA). At optimized conditions, complete conversion of dimethylamine was achieved with more than 92% product yield at 170 degrees C and 13 MPa pressure with a reaction time of 6 h. Key catalyst properties were determined using X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS), CO2-temper-ature programmed desorption (TPD), H-2 temperature-programmed reduction (TPR) and Fourier transform infrared (FTIR). The determination of surface morphology was carried out using field emission scanning electron microscope (FE-SEM) and high-resolution transmission electron microscopy (HR-TEM). At the same time, the chemical composition was verified by energy-dispersive X-ray (EDS). In addition, kinetic modeling is performed using the two site Langmuir-Hinshelwood-Hougen-Watson model. The regressed kinetic parameters gave an appropriate fit with experimental concentration values and activation energy is calculated as 413 kJ/mol K-1.
Keywords: Dimethylformamide; Hydrogenation; hydrotalcite; Langmuir-Hinshelwood-Hougen-Watson model; Supercritical carbon dioxide